Clinical phenotype of severe and moderate haemophilia: Who should receive prophylaxis and what is the target trough level?. Issue 2 (27th February 2021) - Collins, Peter W.; Obaji, Samya G.; Roberts, Heledd; Gorsani, Deepan; Rayment, Rachel
Abstract: Introduction: One of the most often stated tenets of haemophilia care is that prophylaxis converts a person from a severe to a moderate phenotype. In this review, we argue that this is not an accurate assumption and that people on prophylaxis predominantly have factor VIII/IX levels in the mild range. Moderate haemophilia and prophylaxis: People with moderate haemophilia, who are treating with on‐demand regimens, experience joint bleeds and often develop significant arthropathy. This is especially true for people with a baseline level of 1‒3 IU/dl, as first reported 55 years ago, and confirmed in more recent studies. Evidence is emerging suggesting that people with severe haemophilia who are using prophylaxis have better musculoskeletal outcomes than people with moderate haemophilia treated episodically. Trough levels: The debate around the optimum trough level whilst on prophylaxis is ongoing. It is not appropriate to extrapolate information about baseline levels to recommendations about target trough levels on prophylaxis because these are different situations. Studies are emerging that support higher target trough levels than previously used, but in spite of this, the aim of achieving zero bleeds remains elusive with both factor replacement and non‐replacement therapies. Conclusions: We recommend that people with moderate haemophilia, especially those with a baseline of 1–3 IU/dl, should be offered prophylaxis based on the same criteria as people with severe haemophilia. Trough levels should be maintained above 3 IU/dl or higher if a level of 3 IU/dl does not control breakthrough bleeding and prophylaxis should be tailored to the bleeding phenotype. This advice is in line with recently published guidelines from the World Federation of Haemophilia and the UK Haemophilia Centre Doctors' Organisation.